2013
DOI: 10.1155/2013/860467
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiotic Resistance Pattern of Methicillin-ResistantStaphylococcus aureusfrom an Orthopaedic Hospital in Nigeria

Abstract: Patients with surgical wounds have been reported to be at high risk of MRSA carriage and infection. The prevalence and antibiotic resistance pattern of this organism in the orthopaedic ward of Ahmadu Bello University Teaching Hospital (ABUTH), Zaria-Nigeria, a 547-bed Nigerian hospital, were thus studied. A total of 185 isolates of Staphylococcus aureus were confirmed from 217 samples taken from the orthopaedic wards of the hospital using standard isolation methods. Out of these, 44 (23.8%) were from the wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 15 publications
6
22
2
1
Order By: Relevance
“…Data on the prevalence of MRSA is not uniform. Literature has documented a significant variation in the prevalence rate from different parts of India and between countries [1][2][3][4][5][6][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . Studies from India report MRSA prevalence ranging from 6.9% to 87% 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Data on the prevalence of MRSA is not uniform. Literature has documented a significant variation in the prevalence rate from different parts of India and between countries [1][2][3][4][5][6][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . Studies from India report MRSA prevalence ranging from 6.9% to 87% 9 .…”
Section: Discussionmentioning
confidence: 99%
“…MRSA strains exhibit resistance to oxacillin or methicillin and other antimicrobial agents and this has been used in the diagnosis of these strains [4,5]. The emergence of resistance in these strains of S. aureus is mediated by a change in penicillin binding protein (PBP2a) which is encoded by the Mec A gene, resulting to strains with multiple resistance to various antibiotics [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…21 Investigation of Prevalence and antibiotic resistance pattern of methicillin-resistant Staphylococcus aureus in the Orthopaedic Hospital in Nigeria by Udobi et al showed resistance pattern of: ampicillin 100%, pefloxacin 90.9%, ceftriaxone 69.7%, gentamicin 54.5%, and ciprofloxacin 51.5%. 30 The study by Anupriya et al revealed that microbial contamination of mobile phones in a tertiary care hospital was 87.3% and 56.4% among health care workers versus non-health care workers, but there was no MRSA. 31 A Study by Nirmal et al among health-care workers, explained that HA-MRSA carriage was seen in 47 individuals in their nasal vestibules; the colonization rate was 15.1%.…”
Section: Discussionmentioning
confidence: 99%